FRI0037 Clinical and B Cell Subsets Biomarkers of Response to Tocilizumab in Rheumatoid Arthritis. (9th June 2015) - Gremese, E.; Tolusso, B.; Fedele, A.L.; Nowik, M.; Canestri, S.; Ferraccioli, G.
Abstract : Background: Tocilizumab (TCZ) is effective in the treatment of Rheumatoid Arthritis (RA) and it is recognized as a modifier of B cell subsets in vivo, inducing changes over time in the distribution of B cell subpopulation, i.e. regulatory TGF+ B cells and memory B cells. Objectives: To define whether the combination of clinical variables (sex, disease duration, BMI, seropositivity, DAS value) and B cell subsets analysis at baseline could help to define the best responders and to see whether changes after 3 months could predict the occurrence of DAS remission at 3 and 6 months. Methods: 62 consecutive RA patients (75.8% female, average age: 52.9±15.3 years, average disease duration: 8.8±10.4 years, 64.5% ACPA+ and/or IgM-RF+ and 48.4% overweight or obese) who initiated TCZ (8 mg/kg monthly) were recruited. All patients were no responders to conventional disease modifying antirheumatic drugs (DMARDs), including methotrexate, and biologic agents (b-DMARDs; 46.8%). At baseline and every 3 months demographic and immunological data and the ACR/EULAR core data set [erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), swollen joint count (SJC), tender joint count (TJC), physician and patient global assessment, pain, health assessment questionnaire (HAQ)] were recorded. At each visit, clinical improvement and remission were evaluated according to DAS (DAS-R). At baseline and at 6-month follow-up visit peripheral blood samples were collected and analyzed by flow cytometry for the distribution of circulating B cell subsets using IgD/CD27 classification. Results: Mean DAS at baseline was 3.7±0.9. A DAS-R was reached in 28.3% of RA patients at 3 months (T3), 39.7% at 6 months (T6) and 51.0% at 12 months (T12) follow-up. Fifty percent of the ERA patients already had DAS-R compared to 20.5% of LSRA (p=0.03) at T3. The percentage of DAS-R at 3 and 6 months FU was lower in female patients (17.8% at T3 and 29.5% at T6) compared to male patients (60% at T3, p=0.002 and 71.4% at T6, p=0.01) but at T12 the difference was not significant (45.0% vs 72.7%, p=0.11). RA patients with baseline DAS<3.7 reached DAS-R at T3 in 40.6% whereas those with DAS>3.7 reached DAS-R in 14.3% (p=0.02). At T12 the percentages were 64.5% vs 36% (p=0.04), respectively. Being RF and/or ACPA seropositive or having a different BMI, did not influence the outcome at T3 as well as at T6 or at T12. Finally, being smokers predicted a better response at T3 than never-smokers (p=0.02). Considering the B cell subsets, a higher frequency of switched-memory B cells (IgD-CD27+; >20.8%) was associated with DAS-R at T3 (p=0.04) and T6 (p=0.11). This finding was confirmed by the inverse correlation between IgD-CD27+ cell percentages at baseline with DAS value at T3 (R=-0.270; P=0.04) and T6 (R=-0.310; P=0.02). Conclusions: In our RA cohort, being male, having DAS<3.7, being ERA represents the best matrix to predict DAS remission at 3 and 6 months. Disclosure of Interest: None declared